Novel tetrazole and cyanamide derivatives as inhibitors of cyclooxygenase-2 enzyme: design, synthesis, anti-inflammatory evaluation, ulcerogenic liability and docking study - Phoebe F. Lamie; John N. Philoppes; Amany A. Azouz; Nesreen M. Safwat (Taylor & Francis Group, 2017)
Nineteen new compounds containing tetrazole and/or cyanamide moiety have been designed and synthesised. Their structures were confirmed using spectroscopic methods and elemental analyses. Anti-inflammatory activity for all the synthesised compounds was evaluated in vivo. The most active compounds 4c, 5a, 5d-f, 8a and b and 9a and b were further investigated for their ulcerogenic liability and analgesic activity. Pyrazoline derivatives 9b and 8b bearing trimethoxyphenyl part and SO2NH2 or SO2Me pharmacophore showed equal or nearly the same ulcerogenic liability (UI: 0.5, 0.75, respectively), to celecoxib (UI: 0.50). Most of tested compounds showed potent central and/or peripheral analgesic activities. Histopathological investigations were done to evaluate test compounds effect on rat's gastric tissue. The obtained results were in consistent with the in vitro data on COX evaluation. Docking study was also done for all the target compounds inside COX-2-active site.